Assessment of Mental Training Levels of Individual and Team Athletes in Terms of Some Variables - Öznur Yüksel; Özlem Orhan (Journal of Educational Issues, 2024)
The purpose of this study is to examine whether individual and team athletes’ mental training levels differ in terms of variables such as age, gender, sports age and being a national team athlete. This study used quantitative research methods, relational survey and descriptive survey models. A total of 700 individual and team athletes, 358 women (ages 22.48±3.20 years) and 342 men (ages 22.36±18-28 3.27 years), participated in the study voluntarily. “The Sport Mental Training Questionnaire (SMTQ)”, adapted into Turkish by Yarayan and Ilhan (2018), and demographic information form were applied as a data collection tool. Descriptive statistics, independent sample t-test and one-way variance analysis ANOVA tests were used in the analysis and interpretation of the obtained data. After the Anova test, Tukey test was performed as a complementary post-hoc analysis to determine the differences. According to the statistical analysis results, the interpersonal skill scores of persons doing team sports were determined to be higher than those doing individual sports. It was revealed that the scores of male athletes’ mental performance and mental basic skills were higher than that of women athletes while women’s interpersonal skills and self-talking points were higher than men. A statistically significant difference was established in the mental training scores of the athletes according to the variables of age, sports age and being a national team athlete (p < 0.05).